(untitled) (Swiss Medical Weekly, 2011)
Oral devices, in particular Mandibular Advancement Splints (MAS), which hold the mandible in a protruded position during sleep, are increasingly used for the treatment of Obstructive Sleep Apnoea (OSA). These devices can be effective in treating OSA across a range of severity. Complete resolution of OSA (Apnoea-Hypopnoea Index [AHI] reduced <5/hr) with use of an MAS occurs in around 40% of patients. Overall two thirds of patients experience some clinical benefit (≥50% AHI reduction AHI) however others will not objectively respond to this form of treatment, despite improvement in symptoms. Although MAS are less efficacious in reducing polysomnographic indices of OSA than the standard treatment, Continuous Positive Airway Pressure (CPAP), improvements in health outcomes appear to be comparable. Therefore, the superiority of CPAP in improving oxygen desaturations and reducing AHI may be extenuated by its low compliance, resulting in both treatments having similar effectiveness in clinical practice. MAS are now recommended as a first line treatment for mild to moderate OSA, as well as in more severe patients who are unable to tolerate or refuse CPAP. Success with MAS treatment has been associated with factors such as female gender, younger age, supine-dependent OSA, lower BMI, smaller neck circumference and craniofacial factors, however a reliable, validated method for prediction in the clinical setting has yet to be established. MAS are well tolerated, however short-term side effects are common although generally minor and transient. Long-term dental changes are for the most part subclinical, but can be problematic for a minority of patients. MAS are a dental-based treatment for a medical sleep disorder and, as such, an interdisciplinary care model is considered important for the attainment of optimal patient outcomes.